Psychiatric considerations in the oncology setting. (26th May 2015) - Mehta, Reema D.; Roth, Andrew J.
<x xml:space="preserve">Abstract</x> Answer questions and earn CME/CNE An aging population and advances in diagnostics and treatment have resulted in a rapidly growing population of people impacted by cancer. People live longer after a cancer diagnosis and tolerate more aggressive treatments than in the past. Younger patients struggle with diversions from the normal developmental milestones in career and relationships, while older patients deal with the dual challenges of aging and cancer. Cancer's transition from likely death to survival has increased interest in its impact on psychosocial issues and quality of life, rather than just longevity. In this article, the authors review the psychiatric diagnosis and management of the mental health issues most often encountered in oncology. Oncology treatment teams, including oncologists, nurses, social workers, and other ancillary staff, are often on the front lines of addressing psychiatric distress and clinical syndromes when psychiatrists are not easily available. The purpose of this review article is to highlight opportunities for nonpsychiatrists to improve identification and treatment of psychosocial distress and psychiatric syndromes and to request formal psychiatric consultation in appropriate situations. Psychotherapeutic, psychopharmacologic, cognitive, and behavioral‐oriented interventions, as well as supportive interventions, are discussed for treating patients who are facing challenges during active cancer treatment, survivorship, and at the end of life. This review is not exhaustive but highlights the more common psychosomatic medicine and palliative care scenarios that impact cancer patient care. The importance of recognizing and addressing burnout and compassion fatigue in multidisciplinary professionals who care for those treated for cancer is also discussed given the secondary impact this can have on patient care. CA Cancer J Clin 2015;65:299–314. © 2015 American Cancer Society.